2022
DOI: 10.3390/su14116686
|View full text |Cite
|
Sign up to set email alerts
|

A Roadmap for Innovation Capacity in Developing Countries

Abstract: Innovation capacity is a dynamic capacity linked with the achievement of competitive advantage. Several mechanisms have been proposed to evaluate this capacity. However, developing innovation capacity is a complex process, particularly for developing countries, due to the intricacy of its determinants. Hence, this research analyzes the interlinkages between the key determinants driving this capacity to further propose a continuous path for its growth. A comprehensive review of the literature regarding assessin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 143 publications
(256 reference statements)
1
4
0
Order By: Relevance
“…Furthermore, FDI and its flow intensify the regulation of the domestic market, favoring the renewable energy scenario. In parallel with the results obtained, the literature indicates that capital flows can be determinant for companies focused on the energy sector to be able to innovate through specific capabilities in contexts that lack regulations to accommodate technologies such as offshore wind or energy storage (Azam & Haseeb, 2021;Novillo-Villegas et al, 2022). This association matches our Propositions 1 and 2.…”
Section: Foreign Direct Investment Blocksupporting
confidence: 86%
See 2 more Smart Citations
“…Furthermore, FDI and its flow intensify the regulation of the domestic market, favoring the renewable energy scenario. In parallel with the results obtained, the literature indicates that capital flows can be determinant for companies focused on the energy sector to be able to innovate through specific capabilities in contexts that lack regulations to accommodate technologies such as offshore wind or energy storage (Azam & Haseeb, 2021;Novillo-Villegas et al, 2022). This association matches our Propositions 1 and 2.…”
Section: Foreign Direct Investment Blocksupporting
confidence: 86%
“…The varied perspectives in the literature about IC carry several elements in common (Tang, 1998;Wang and Ahmed, 2007;Smith et al, 2008;Vasconcelos, 2008;Novillo-Villegas, Ayala-Andrade, Lopez-Cox, Salazar-Oyaneder, & Acosta-Vargas, 2022). In this paper, categorical concepts will be emphasized according to Valladares, Vasconcellos, and Di Serio (2014) The concept of People Management for Innovation is linked to practical studies of organizational culture and social structures and reflects the autonomy acquired through leadership and how it impacts the relationship with employees, promotes freedom to innovate, and gives room to new, challenging goals that can be achieved by compiling different ideas and knowledge (Amabile, Schatzel, Moneta and Kramer, 2004).…”
Section: Innovation Capacity and The Organization's Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the study further revealed that innovation implementation showed high dependence but low driving power, whereas strategic resources acted as a linkage factor. Using the ISM-MICMAC approach (Novillo-Villegas et al ., 2022; Hajiagha et al ., 2022), showed that the promotion and protection of innovation and intellectual property are relevant in paving the way for the development of innovation capacity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For high market saturation (F6), this study indicates that the managerial authorities of the manufacturing industry have limited knowledge about the market and their competitors. Therefore, firms hesitate to take the next step toward the open innovation process due to insufficient knowledge about the market(Novillo-Villegas et al ., 2022). The factors of level 3 lead to level 2.…”
Section: The Construction Of the Structural Self-interaction Matrix (...mentioning
confidence: 99%